ATM acts downstream of ATR in the DNA damage response signalling of bystander cells - Burdak-Rothkamm, Susanne (2008)
This study identifies ataxia-telangiectasia mutated (ATM) as a further component of the complex signalling network of radiation-induced DNA damage in non-targeted bystander cells downstream of ataxia-telangiectasia and Rad3-related (ATR) and provides a rationale for molecular targeted modulation of these effects. In directly irradiated cells ATR, ATM and DNA-PK deficiency resulted in reduced cell survival as predicted by the known important role of these proteins in sensing DNA damage. A decrease in clonogenic survival was also observed in ATR/ATM/DNA-PK proficient, non-irradiated bystander cells, but this effect was completely abrogated in ATR and ATM but not DNA-PK deficient bystander cells. ATM activation in bystander cells was found to be dependent on ATR function. Furthermore, the induction and co-localisation of ATR, 53BP1, ATM-S1981P, p21 and BRCA1 foci in non-targeted cells was demonstrated, suggesting their involvement in bystander DNA-damage signalling and providing additional potential targets for its modulation. 53BP1 bystander foci were induced in an ATR dependent manner predominantly in S-phase cells, similar to γH2AX foci induction. In conclusion these results provide a rationale for the differential modulation of targeted and non-targeted effects of radiation.